PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL PEMEDIASI - Agustini, Ni Putu Lady; Dewi, I.G.A. Manuati; Subudi, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The aim of this study is to determine the mediating role of organizational commitment on the influence of perceived organizational support on turnover intention of the employees of RSK Bedah BIMC Kuta. The number of sample is 62 employees are determined by disproportionate stratified random sampling method . Data were collected by distributing questionnaires and analyzed using Partial Least Square and Sobel test. The result showed that perceived organizational support and organizational commitment negatively affect turnover intention, perceived organizational support positively influence organizational commitment and organizational commitment mediated the influence of perceived organizational support on turnover intention. The results of this study are expected to be taken into consideration for Management RSK Bedah BIMC Kuta to reduce the level of turnover by making policies and decisions related to organizational support where employees feel cared about and appreciated by organizations that fosters employee commitment to the organization so employee will not  have plan to leave organization.
Keywords: perceived organizational support, organizational commitment, turnover intention